Preclinical extracellular matrix-based treatment strategies for myocardial infarction: a systematic review and meta-analysis - Atze van der Pol; Marijn C. Peters; Ignasi Jorba; Anke M. Smits; Niels P. van der Kaaij; Marie-Jose Goumans; Kimberley E. Wever; Carlijn V. C. Bouten (Communications Medicine)
Abstract Background Administrating extracellular matrix (ECM) to restore cardiac function post-myocardial infarction (MI) shows promise, however study variability obscures its true impact. We therefore conducted a systematic review and meta-analysis of preclinical studies to assess the effects of ECM treatments on cardiac function and tissue homeostasis post-MI. Methods We searched PubMed and SCOPUS from inception to June 28, 2024, for animal studies describing ECM treatment post-MI (pre-registered on PROSPERO, CRD42022368400). Random effects meta-analyses compared ECM treatment to controls regarding left ventricular ejection fraction (LVEF), fractional shortening, infarct size, stroke volume, and left ventricular wall thickness. Subgroup analyses examined the influence of sex, species, ECM source, and administration method. Funnel plots and Egger’s regression assessed publication bias. Results We identify 88 articles which meet our inclusion criteria. These studies describe the use of rats (51%), mice (38%), and pigs (11%). 44% of studies use males, 34% females, 5% both sexes, and 17% did not report sex. Most studies employ permanent MI models (85%) over ischemia reperfusion models (15%), and deliver ECM via intramyocardial injection (59%), cardiac patch (39%), cardiac sleeve (1%), or osmotic pump (1%). Our meta-analysis demonstrates that ECM treatment significantly improves LVEF (MD: 10.9%, 95% CI: [8.7%;13.0%]; p = 8.057e-24), fractional shortening (MD: 8.2%, 95% CI: [5.6%; 10.9%]; p = 1.751e-09), stroke volume (SMD 0.6, 95% CI: [0.2;1.0], p = 0.004), left ventricular wall thickening (SMD 1.2, 95% CI: [0.9; 1.5], p = 1.321e-17), while reducing infarct size (-11.7%, 95% CI: [-14.7%;-8.6%], p = 3.699e-14). We find no significant differences between the various subgroups and no indication of publication bias. Conclusions ECM-based treatments significantly enhance cardiac function and tissue homeostasis in preclinical post-MI models, supporting further research toward clinical translation.